What are the consequences of regularizing undocumented immigrants? - Sherrie A. Kossoudji (IZA World of Labor, 2016)
Millions of people enter (or remain in) countries without permission as they flee violence, war, or economic hardship. Regularization policies that offer residence and work rights have multiple and multi-layered effects on the economy and society, but they always directly affect the labor market opportunities of those who are regularized. Large numbers of undocumented people in many countries, a new political willingness to fight for human and civil rights, and dramatically increasing refugee flows mean continued pressure to enact regularization policies.
Keywords: J62; J68; J48; 330; immigration reform; worker legal status; regularized workers; legalized workers; amnesty denial